Spinal Muscular Atrophy 5q under the Mask of Myopathy: 10 Clinical Cases - Sergei A. Kurbatov ("Paediatrician" Publishers LLC, 2021)
Background. Spinal muscular atrophy 5q (5q SMA) is the most frequent autosomal recessive hereditary neuromuscular disease. Molecular genetic testing is used for SMA diagnosis, and it can confirm only 5q SMA. The clinical findings and results of paraclinical studies may overlap with hereditary primary-muscular diseases making the diagnosis difficult and delaying the administration of pathogenetic treatment for 5q SMA.Clinical case description. Clinical description of 10 patients with 5q SMA aged from 3 months to 25 years with different severity of proximal tetraparesis, skeletal muscular atrophy and tendon reflexes depression is given. 3 patients under 2 years of age with myogenic pattern at needle electromyography (nEMG) in lateral vastus muscle and 7 patients over 2 years of age with increased levels of creatine phosphokinase (CPK) in blood serum were mistakenly diagnosed for inherited primary-muscular diseases for the period from 1 month to 12 years. After the genetic counselling based on the disease course and clinical findings we suspected and later confirmed 5q SMA.Conclusion. In case of flaccid proximal tetraparesis associated with myogenic pattern at nEMG in young children or with increased CPK levels at late manifestation it is crucial to perform differential diagnosis of 5q SMA since there are options of pathogenetic therapy.